US and EU Supply Chain Strategies to the Food Quality and Security Standards in Russia - L.G. Chuvakhina; G.A. Terskaya; I.V. Koroleva; N.N. Solovykh; P.I. Chuvakhin (International Journal of Supply Chain Management, 2019)
Abstract-Supply chain management strategy plays an important role in agriculture industry which is the most complex topic in negotiations between the United States and the European Union on the agreement to establish the Transatlantic Trade and Investment Partnership. This paper describes the US activity on greater access of American corporations on the European market and differences in approaches of the US and the EU to the quality and security food standards and to the use of genetically modified foods. Strained relationships between the US and the EU in 2016 is a result of the publication of the US intentions to secretly push American standards and rules into the draft agreement. That would mean deviation from the European agricultural regulatory requirements that is why it has caused a backlash among European partners.